Comparison of Surgical Complications Rates Between LigaSure Small Jaw and Clamp-and-Tie Hemostatic Technique in 1,000 Neuro-Monitored Thyroidectomies - Liu, Cheng-Hsin; Wang, Chih-Chun; Wu, Che-Wei; Lin, Yi-Chu; Lu, I-Cheng; Chang, Pi-Ying; Lien, Ching-Feng; Wang, Chien-Chung; Hwang, Tzer-Zen; Huang, Tzu-Yen; Chiang, Feng-Yu (Frontiers in Endocrinology, 2021)
Over the past decade, the use of neuromonitoring in thyroid surgery has become well established and is increasing accepted across the world. In addition, new developments in energy devices have significantly improved efficacy in achieving hemostasis in thyroid surgery. Few studies focused on the complication rates in energy device-assisted sutureless neuro-monitored thyroidectomy. This study investigates a novel LigaSure Small Jaw (LSJ) technique for sutureless thyroidectomy and compares the major complication rates between LSJ and conventional clamp-and-tie technique in one thousand consecutive neuro-monitored thyroidectomy patients. Five hundred patients received sutureless thyroidectomy performed with LSJ (Group L), and 500 patients received surgery performed with conventional clamp-and-tie technique (Group C). Complication rates of postoperative hematoma, hypocalcemia and recurrent laryngeal nerve (RLN) palsy were compared between groups. The overall complication rates of hematoma, hypocalcemia (temporary/ permanent), and RLN (temporary/ permanent) palsy were 0.9%, 24.9% (24.6%/0.3%), and 1.7% (1.5%/0.2%), respectively. Group L and Group C significantly differed in postoperative hematoma rate (0.0% vs. 1.8%, respectively; p = 0.0026) and in postoperative hypocalcemia rate (20.1% vs. 30.0%, respectively; p = 0.0032). The incidence of RLN palsy did not significantly differ between Group L and Group C (1.38% vs. 2.08%; p = 0.2652). The overall major complication rates are low in neuro-monitored thyroidectomy. The LSJ is feasible for performing completely sutureless thyroidectomy and obtains superior outcomes of postoperative hematoma and hypocalcemia in comparison with clamp-and-tie hemostatic technique. The novel LSJ technique using double or overlapped sealing is useful for sutureless thyroidectomy. However, surgeons must carefully observe the tissue contraction that may reduce the LSJ-RLN distance and increase the risk of thermal injury during the LSJ activation.